SERAGAM LORENG YANG TERCORENG AKIBAT PEMBUNUHAN BERENCANA YANG DILAKUKAN OLEH ANGGOTA TNI : STUDI PUTUSAN PENGADILAN MILITER I-03 PADANG NOMOR 60-K/PM.I-03/AL/VIII/2024 - Joko Winarta; Subhan Zein Sgn (LEX OMNIBUS : Jurnal Hukum Tata Negara dan Administrasi Negara, 2025)
Crimes occurring within society are diverse in nature, one of which is homicide. Acts of homicide can be perpetrated by anyone, including members of the Indonesian National Armed Forces (TNI). When committed by military personnel, such crimes not only impact the victims and their families but may also tarnish the reputation of the military institution as a whole if not addressed professionally and in accordance with applicable legal standards. This study employs a normative juridical method with a case-based approach. The regulation concerning premeditated murder is stipulated in Article 340 of the Indonesian Criminal Code (KUHP), which prescribes a sentence of life imprisonment or the death penalty. In the 2023 revision of the KUHP, this provision is contained in Article 459, maintaining the same penalties. However, the Indonesian Military Criminal Code (KUHPM) does not regulate premeditated murder. In the case Number 60-K/PM.I-03/Al/VIII/2024, the Panel of Judges at the Military Court I-03 Padang sentenced the defendant to life imprisonment and imposed an additional penalty of dishonorable discharge from military service. The imposition of the maximum sentence for premeditated murder is essential in generating significant social and psychological deterrent effects. Academic studies, empirical research, and scientific publications should be encouraged as forms of social control over military legal practices to ensure that the principle of equality before the law is upheld. The TNI must continuously enhance the mental, psychological, and professional ethical development of all its personnel.